EVALUASI PROGRAM KAMPUNG ZAKAT DALAM MENINGKATKAN KESEJAHTERAAN MUSTAHIK DESA TAMANSARI KECAMATAN KARANGMONCOL PURBALINGGA (Studi pada LAZISMU Purbalingga) - Naelul Arifah; Kholilur Rahman (JOURNAL SAINS STUDENT RESEARCH, 2025)
Poverty remains a major challenge in national development, including in Purbalingga Regency, where the poverty rate exceeds the Central Java provincial average. Since 2021, LAZISMU Purbalingga has implemented the Kampung Zakat (Zakat Village) Program in Tamansari Village as an initiative to improve the welfare of mustahik through productive zakat-based empowerment. This study aims to evaluate the effectiveness of the program using the CIPP model (Context, Input, Process, Product) combined with the Islamic welfare theory.This research employed a qualitative descriptive method using interviews, observation, and documentation. The results indicate that the Kampung Zakat program aligns with community needs and positively affects mustahik welfare. Economic aspects improved through productive business activities, social aspects through increased community participation, and spiritual aspects through growing religious awareness. However, mentoring and monitoring activities need to be strengthened to ensure the sustainability of welfare outcomes.